Blood in the water: DNA barcoding of traded shark fins in Singapore - Drescher, Lynn; Heng, Noel Jin Kiat; Chin, Min Yi; Karve, Neel R. O.; Cheung, Edward Jun Wei; Kurniadi, Anastasia; Urera, Mariana Quesada; Waldeck, Felipe Gabriel; Dharshini, U.; Hoe, Nirel Tze En; Choo, Joshua Song Yang; Lok, Russell Fock Jun; et al. (Frontiers in Marine Science, 2022)
Due to overfishing and shark finning, global shark populations have declined significantly, with estimates suggesting reductions of approximately 90% have occurred over the last 50 years. Singapore is a major shark fin transhipment hub that supplies global markets helping to satisfy the demand for shark fins that are seen as status symbols, and are reputed to have medicinal value in Asian culture. Despite the recognised and urgent need to better protect shark populations, the success of such efforts has been limited by the difficulties associated with visually identifying the species of shark that a fin came from. In this study, we collected 452 shark fin tissue samples from a variety of local markets in Singapore. Using DNA barcoding techniques, we amplified a 350 base pair fragment of the mitochondrial cytochrome c oxidase subunit I (COI) gene from each to identify the species sold in Singapore. We identified 22 species of shark, of which 17 are categorised as threatened (critically endangered, endangered or vulnerable) under the IUCN Red List. Six of these species are also listed on Appendix II of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). We hope these findings will be useful in the enforcement of current trade regulations, and help in the design of future policy seeking to protect shark populations from unsustainable practices.